Storytelling as 'unorthodox' agency: Negotiating the 2012 family immigration rules (United Kingdom). (August 2017) - Beattie, Amanda Russell
This article attends to the lived experience of binational families subject to the 2012 family immigration rules (FIR). It seeks to enrich the pre-existing discussions of family migration within the European Union (EU) and the United Kingdom, focusing on the 'micro-political' experiences of those whose lives have been adversely affected by their introduction. It draws on the life writings of binational families, suggesting that a micro-political focus reveals an ongoing neuropolitical experience that traditional accounts of moral agency are ill-equipped to negotiate. The article suggests an unorthodox interpretation of agency premised on storytelling, while probing the tensions that emerge when this lived experience is framed in such a manner. It concludes by positing a series of questions relating to the value of a neuropolitical labelling of the subject and suggests a need to further engage with traumatic interpretations of harm at the intersection of citizenship rights and mobility rights.